Upaya Meningkatkan Literasi Anak–Anak Berbasis Pendidikan Agama Islam Di Desa Pagar Manik - Annaafi, Ahmad Danu; Yuris, Evicenna (Yayasan Rahmat Islamiyah, 2024)
This article was written with the aim of increasing children's literacy based on Islamic religious education in Pagar Manik Village. Low interest in reading and writing, minimal access to relevant reading materials, and lack of parental support in supporting children's literacy are the main problems in this village. This program is designed to integrate Islamic religious values into literacy activities, so that it not only improves children's reading and writing skills, but also forms characters with good morals. The methods used include providing religious-based literacy classes, training for parents, and providing a reading corner with relevant books. The results of this program show an increase in children's interest and literacy skills, as well as more active parental involvement in supporting literacy activities at home. Overall, this program has succeeded in making a positive contribution in increasing the literacy and religious understanding of children in Pagar Manik Village, and is expected to be sustainable through the active participation of the local community.